A Watermarking Scheme for Digital Images Using Multilevel Wavelet Decomposition - Shaikh, Muhammad Shafique; Dote, Yasuhiko (Malaysian Journal of Computer Science, 2003)
A robust multilevel watermarking method based on multiresolution wavelet transformation is introduced. The coefficients of watermark are embedded into those of host image at different transformation level with a novel procedure. Watermark is extracted by inverse transformation at every level and by feeding the residual marked image to the subsequent level. Finally, the watermark is estimated by taking mean value of the watermarks obtained at every level. The introduced method is tested on six gray images with added Gaussian, salt and pepper, Speckle, and JPEG noises. The method is also examined with a color mpeg video. Signal to noise ratio with correlation coefficients are used as criteria for testing the method.